# SOLUTION: The expression(-1+i)^3 is equivalent to (1) -3i (2) -2-2i (3) -1-i (4) 2+2i ---------------------------------------------------------------------------------- please choose

Algebra ->  Algebra  -> Complex Numbers Imaginary Numbers Solvers and Lesson -> SOLUTION: The expression(-1+i)^3 is equivalent to (1) -3i (2) -2-2i (3) -1-i (4) 2+2i ---------------------------------------------------------------------------------- please choose       Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Complex Numbers Solvers Lessons Answers archive Quiz In Depth

 Question 233419: The expression(-1+i)^3 is equivalent to (1) -3i (2) -2-2i (3) -1-i (4) 2+2i ---------------------------------------------------------------------------------- please choose the correct answer choice and explain how to get the answer Thank youAnswer by Alan3354(30993)   (Show Source): You can put this solution on YOUR website!The expression(-1+i)^3 is equivalent to (1) -3i (2) -2-2i (3) -1-i (4) 2+2i ----------- (-1+i)^2 = 1-1 - 2i = -2i (-1+i)^3 = -2i*(-1+i) = 2i + 2 = 2+2i --> #4 ---------------- -1+i = sqrt(2)cis135 (-1+i)^3 = 2sqrt(2)cis405 = 2sqrt(2)cis45 = 2sqrt(2)*(cos(45) + isin(45)) = 2 + 2i Same answer